A clinical study of laparoscopic versus open umbilical hernia repair - D.M., Abhinava; Naik C, Shashidhar; Rao K, Seshagiri; C.S., Santhosh; N Manangi, Mallikarjuna; Nagaraj, Niranjan (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2017)
Background: Umbilical Hernia is one of the most common surgical problems. Since the prosthetic repair has become the standard of practice for inguinal hernia management, the same has been adapted for Umbilical hernia management with better outcome. There is still debate going on regarding the better surgical approach. There are very few prospective studies comparing the laparoscopic and open method of Umbilical hernia mesh repair. This study compared the short term outcomes following laparoscopic versus open mesh repair of Umbilical hernia. Methods: Patients who underwent Umbilical hernia repair at Victoria hospital, Bengaluru between July 2015 to January 2017 were studied. Patients were divided into two groups, those who underwent Laparoscopic repair were considered into “group A” and those who underwent Open repair were considered into “group B”. Both the groups were compared with respect to Duration of surgery, Use of Drains, complications like wound infection, seroma, and haematoma, Return to normal activity, Duration of hospital stay. Results: A total of 96 patients underwent umbilical hernia repair out of which 88 were included as 8 patients underwent primary suture repairs.Out of 88 patients 49(55.68%) patients underwent Laparoscopic mesh repair [Group A] and 39(44.32%) patients underwent open mesh repair. Duration of surgery is relatively less in Group B, Use of Drains, Complications like wound infection, seroma and haematoma is significantly less in Group A, Duration of hospital stay is relatively less in Group A, Return to normal activity is faster in Group A. Conclusion: Laparoscopic umbilical hernia repair is a safe and effective technique. Laparoscopic mesh repair required in shorter duration of surgery, less use of postoperative drains, faster return to normal activity and less complications rate, shorter hospital stay.